2023
DOI: 10.1002/app.54436
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of modified polylactic acid fiber containing anti‐hydrolysis agents

Abstract: Polylactic acid (PLA) is a promising alternative to petroleum‐based polymers due to its biodegradability. However, its low mechanical properties in the presence of moisture are a challenge for textile applications. In this study, we investigated the effects of two anti‐hydrolysis agents, an epoxy‐based agent (ADR) and an aromatic carbodiimide‐based agent (ZIKA), on the mechanical properties and hydrolysis resistance of PLA fibers. A melt‐spinning process was used to prepare anti‐hydrolysis fibers by adding 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…Thus, the reduction of the number average molecular weight for the samples with 2.0% pCDI was only 25%. This is consistent with other studies in which carbodiimides were used for stabilization [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In some cases, however, even lower molecular weight reductions were observed during hydrolytic aging [ 29 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the reduction of the number average molecular weight for the samples with 2.0% pCDI was only 25%. This is consistent with other studies in which carbodiimides were used for stabilization [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. In some cases, however, even lower molecular weight reductions were observed during hydrolytic aging [ 29 ].…”
Section: Resultssupporting
confidence: 92%
“…One class of additives that reacts with moisture and the carboxyl end groups is defined as hydrolysis inhibitors. Primarily, carbodiimides are used here, which have already been studied many times in PLA [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. They are commercially available in various structural configurations (monomeric, polymeric, aliphatic, aromatic, cyclic).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6, the crystallization rates of PLA systems were analyzed by examining the slope of the double-ln curves. It was observed that the slope of CPLA systems increased after the addition of HNA, which indicated an increase in crystallization rate [52]. Crystallization rate of PLA systems was analyzed according to half crystallization time (t 1/2 ).…”
mentioning
confidence: 99%
“…PET fibres offer high durability and are resistant to moisture, mildew, and most chemicals. PLA[58][59][60][61] fibres are derived from renewable resources, making them environmentally friendly. They offer good comfort, softness, and breathability.…”
mentioning
confidence: 99%